Forged cheques: duties of paying and collecting banks / Abd. Malek Ahmad - Ahmad, Abd. Malek (Faculty of Law, 1985)
The thought of writing this paper first entered my mind, after a series of discussion with an accountant friend. It proved very stimulating, especially in relation to "forgeries" in bank’s. As was rightly pointed out by my friend, very few text books are written specifically on this aspect. only then did I appreciate the importance for Malaysians to undertake authentic research into local banking practice. Banking practice is constantly changing to meet the needs of complex modern society, Accordingly we should not accept practice elsewhere in toto, without knowledge of local legislation and local cases.